1995
DOI: 10.1111/j.1440-1827.1995.tb03392.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of irnmunoreactivities to 75 kDa nerve growth factor receptor, trk gene product and phosphotyrosine in granular cell tumors

Abstract: Nineteen granular cell tumors (GCT) of adults, two congenital granular cell epulides and five epulides fibrosae were immunohistochemically examined to detect the expression of 75 kDa nerve growth factor receptor (NGFR), trk gene product, phosphotyrosine (PT), protein gene product 9.5 (PGP9.5) and S-100 protein. The NGFR-immunoreactivity (IR) and trk gene product-IR were expressed on almost all granular cells of GCT. PT-IR was also demonstrated on granular cells of all GCT examined, although the frequency of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…PGP9.5 and NGFR/p75 had been previously studied in only two lesions [23], with results similar to ours, i.e., the granular cells were found to be PGP9.5 positive and NGFR/p75 negative. NKI/C3 and inhibin-α had not been investigated before in CGCE: our results revealed that the granular cells were positive for NKI/C3 but negative for inhibin-α.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…PGP9.5 and NGFR/p75 had been previously studied in only two lesions [23], with results similar to ours, i.e., the granular cells were found to be PGP9.5 positive and NGFR/p75 negative. NKI/C3 and inhibin-α had not been investigated before in CGCE: our results revealed that the granular cells were positive for NKI/C3 but negative for inhibin-α.…”
Section: Discussionsupporting
confidence: 90%
“…Table 4 summarizes the results derived from the English-language literature of the most common markers that have been used for this purpose. The table includes only studies that have been performed since 1990 as it coincides with the standardization of the laboratory techniques of immunohistochemistry [2,6,8,[20][21][22][23][24][25][26][27][28][29]. There are a total of 13 previous studies on 28 lesions and the five additional lesions from the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tumor is a variant of the granular cell tumor and is S-100 negative immunohistochemically and does not show any differentiation specific to any cell type (1,10). Our case was also negative with the S-100 immune marker.…”
Section: Discussionmentioning
confidence: 73%
“…The etiology and histogenesis of the tumor are controversial. Newborn GCT is a different entity than in the adult with different immunohistochemical features (1). We present a rare case of newborn GCT and review the literature.…”
Section: Introductionmentioning
confidence: 95%